2021
DOI: 10.2147/ndt.s322114
|View full text |Cite
|
Sign up to set email alerts
|

Association Between ZNF804A Gene rs1344706 Polymorphism and Brain Functions in Healthy Individuals: A Systematic Review and Voxel-Based Meta-Analysis

Abstract: Objective Zinc finger protein 804A (ZNF804A) protein participates in embryonic neural repair and development. The single nucleotide polymorphism rs1344706 in ZNF804A gene is closely related to functional abnormalities of the human brain. However, these results are inconsistent. This association was verified by meta-analysis in this study. Methods Fifteen studies on functional magnetic resonance imaging involving 1710 healthy individuals were included in the systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…According to the method of Li et al [ 15 ], the included studies had to meet the following criteria: a) the original data were in published studies that assessed the relationship between the rs6313 polymorphism of the 5-HTR2A gene and antipsychotic drug efficacy; b) the subjects of the original study were patients with schizophrenia and other psychotic disorders or affective disorders; c) during the experiment, all subjects took antipsychotic drugs orally, and no longer received any other antipsychotic treatment; d) in the original study, drug efficacy was evaluated by the Positive and negative symptom scale (PANSS), Brief psychiatric rating scale (BPRS), Clinical global impression (CGI), Global assessment scale (GAS), Scale for the assessment of negative symptoms (SANS), and prior criteria, and the reduction rate was evaluated or patients were divided into responders and non-responders according to the reduction rate; e) the statistical methods of the original study were appropriate, and there were clear genotype or allelic frequency data. Referring to the method of Yang et al [ 16 ], a study was excluded if: a) it was a review, a conference abstract, a commentary, a news reports or other similar type of publication; b) it was a repeated publications; c) it had incomplete or insufficient data; d) it was irrelevant.…”
Section: Methodsmentioning
confidence: 99%
“…According to the method of Li et al [ 15 ], the included studies had to meet the following criteria: a) the original data were in published studies that assessed the relationship between the rs6313 polymorphism of the 5-HTR2A gene and antipsychotic drug efficacy; b) the subjects of the original study were patients with schizophrenia and other psychotic disorders or affective disorders; c) during the experiment, all subjects took antipsychotic drugs orally, and no longer received any other antipsychotic treatment; d) in the original study, drug efficacy was evaluated by the Positive and negative symptom scale (PANSS), Brief psychiatric rating scale (BPRS), Clinical global impression (CGI), Global assessment scale (GAS), Scale for the assessment of negative symptoms (SANS), and prior criteria, and the reduction rate was evaluated or patients were divided into responders and non-responders according to the reduction rate; e) the statistical methods of the original study were appropriate, and there were clear genotype or allelic frequency data. Referring to the method of Yang et al [ 16 ], a study was excluded if: a) it was a review, a conference abstract, a commentary, a news reports or other similar type of publication; b) it was a repeated publications; c) it had incomplete or insufficient data; d) it was irrelevant.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the functional connectivity between the hippocampus and the dorsolateral prefrontal cortex is impaired (Zhang et al 2018). This gene has also been associated with dorsolateral prefrontal cortex coupling with the hippocampus and prefrontal cortex (Rasetti et al 2011;Zhao et al 2020;Yang et al 2021). Finally, a recent study has identified a genetic interaction effect between CACNA1C and ZNF804A modulating the activity ventral caudate medially and within the left hemisphere, the superior and inferior orbitofrontal gyrus, the superior temporal pole and the ventral-anterior insula during a working memory task (Guardiola-Ripoll et al 2022).…”
Section: Impact Of Neurodevelopmental Disturbances On Brain Connectiv...mentioning
confidence: 99%